Cardiovascular–renal axis disorders in the domestic dog and cat: a veterinary consensus statement. (September 2015) - Pouchelon, J. L.; Atkins, C. E.; Bussadori, C.; Oyama, M. A.; Vaden, S. L.; Bonagura, J. D.; Chetboul, V.; Cowgill, L. D.; Elliot, J.; Francey, T.; Grauer, G. F.; Luis Fuentes, V.; et al.
<x xml:space="preserve">Abstract</x> OBJECTIVES There is a growing understanding of the complexity of interplay between renal and cardiovascular systems in both health and disease. The medical profession has adopted the term "cardiorenal syndrome" (CRS) to describe the pathophysiological relationship between the kidney and heart in disease. CRS has yet to be formally defined and described by the veterinary profession and its existence and importance in dogs and cats warrant investigation. The CRS Consensus Group, comprising nine veterinary cardiologists and seven nephrologists from Europe and North America, sought to achieve consensus around the definition, pathophysiology, diagnosis and management of dogs and cats with "cardiovascular‐renal disorders" (CvRD). To this end, the Delphi formal methodology for defining/building consensus and defining guidelines was utilised. METHODS Following a literature review, 13 candidate statements regarding CvRD in dogs and cats were tested for consensus, using a modified Delphi method. As a new area of interest, well‐designed studies, specific to CRS/CvRD, are lacking, particularly in dogs and cats. Hence, while scientific justification of all the recommendations was sought and used when available, recommendations were largely reliant on theory, expert opinion, small clinical studies and extrapolation from data derived from other species. RESULTS Of the 13 statements, 11 achieved consensus and 2 did not. The modified Delphi approach worked well to achieve consensus in an objective manner and to develop initial guidelines for CvRD. DISCUSSION The resultant manuscript describes consensus statements for the definition, classification, diagnosis and management strategies for veterinary patients with CvRD, with an emphasis on the pathological interplay between the two organ systems. By formulating consensus statements regarding CvRD in veterinary medicine, the authors hope to stimulate interest in and advancement of the understanding and management of CvRD in dogs and cats. The use of a formalised method for consensus and guideline development should be considered for other topics in veterinary medicine.